Making Wilderness: An Inquiry into Stig Wesslén’s Documentation and Representation of the Northern Swedish Landscape - Lång, Henrik; Mårland, Erland; Nordlund, Christer (Journal of Northern Studies, 2016)
The present article explores images of the Northern Swedish landscape, produced and mediated by Stig Wesslén (1902–1987) in the 1930s and 1940s. Trained as a forester, Wesslén gradually turned into a documentarist, focusing on the wilderness, notably big birds, predators and the mountain range in Lapland. Along with making a number of ambitious movies and embarking on intensive lecture tours, he was an active debater and writer and published six, richly illustrated books. These careers were interwoven, partly for practical reasons; income from lecturing and journalism financed his filmmaking and gave him time to write his books. It is argued in the article that Wesslén was driven by a strong feeling for wilderness and that he was against the way modern civilization exploited nature. The goal of his documentary work was ultimately to raise public awareness regarding the state of nature and he may thus be seen as a link between the preservationists of the early twentieth century and the environmentalists of the 1960s. In order to reveal the true essence of nature, Wesslén developed a “scientific” documentary technique, which he called “camera hunting.” The idea was to use the best camera equipment possible that would allow him to observe nature at a distance, not disturb the natural order of things, and present authentic images. Yet, as the article shows, Wesslén sometimes anthropomorphized the animals and also dramatized nature in many of his works.